Diagnostic and pathogenetic significance of apolipoprotein disorders in patients with alcoholic fatty liver - Mladenović, Bojan I; Brzački, Vesna; Benedeto-Stojanov, Daniela; Mladenović, Nikola (Vojnosanitetski pregled, 2017)
Background/Aim. Alcohol is the most common cause of fatty liver. Alcohol metabolism takes place in the liver by alcohol dehydrogenase, to toxic acetaldehyde, with fatty acids accumulation in the liver as a consequence. By daily intake of the amount greater than 80 g/day for men and 20 g for women, there is the risk for developing the alcoholic fatty liver (AFLD). The aim of this study was to determine the profile of atherogenic factors in plasma of patients with AFLD compared to patients with non-alcoholic fatty liver (NAFLD) and determine its diagnostic significance. Methods. The study included 74 patients with AFLD who consumed alcoholic beverages daily in large quantities and over 80 g [for men: 3–4 units (U) of alcohol and for women 2–3 U]; the control group consisted of 70 patients with NAFLD verified with ultrasound. A total holesterol (TC), triglycerides (TG), high-density lipoprotein cholesterol (HDL-C), low-density lipoprotein cholesterol (LDL-C) and apoliporoteins (ApoA1 and ApoB) were determined and the ratios TC/HDL-C, ApoB/ApoA1 and LDL-C/HDL-C were calculated. Results. The study included two group: 74 AFLD patients (21% of women and 79% of men), mean age 42.65 ± 9.73 years, who consumed alcoholic beverages daily in the amounts of 80 g, or greter, during the average 2.31 ± 0.96 years and 70 patients with NAFLD (37.5% of women and 63.5% of men) with the average 41.3 ± 4.1 years. There was no significant difference in gender distribution and the average age between the examined groups. Higher values of TG – 9.94 ± 2.94 mmol/L, TC 14.53 ± 2.81 mmol/L, LDL-C 8.57 ± 2.15 mmol/L and ApoB 3.97 ± 0.28 g/L and lower values of HDL-C 0.43 ± 0.11 mmol/L, Apo A1 0.49 ± 0.09 g/L and ApoB/ApoA1 ratio 2.43 ± 1.27 were registered in the AFLD group compared to those registered in the NAFLD group, (TG 8.74 ± 2.54 mmol/L TC 9.87 ± 2.36, LDL-C 6.72 ± 1.98 mmol/L, Apo B 2.38 ± 0.16 g/L, HDL-C 0.78 ± 0.09 mmol/L, Apo A1 0.98 ± 0.04 g/L and ApoB/ApoA1 ratio 7.81±1.42). There were no differences in albumin concentration, international normalized ratio (INR) and values of haemoglobin and haematocrit between the groups. Conclusion. Lipids and the ApoB/ApoA1 ratio, besides markers of hepatocelular damage, can serve as a diagnostic criteria for the presence of AFLD, and as a better indicator of atherogenic risk.
Keywords: liver disease; alcoholic; non-alcoholic fatty liver disease; risk factors; apolipoproteins a; apolipoproteins b; lipids; diagnosis; alcohol drinking